Low Circulating Protein C Levels Are Associated with Lower Leg Ulcers in Patients with Diabetes. (2nd January 2013) - Whitmont, K.; Fulcher, G.; Reid, I.; Xue, M.; McKelvey, K.; Xie, Y.; Aboud, M.; Ward, C.; Smith, M. M.; Cooper, A.; March, L.; Jackson, C. J.
Abstract : Activated protein C (APC) promotes angiogenesis and reepithelialisation and accelerates healing of diabetic ulcers. The aim of this study was to determine the relationship between the incidence of lower leg ulcers and plasma levels of APC's precursor, protein C (PC), in diabetic patients. Patients with diabetes who had a lower leg ulcer(s) for >6 months (n = 36 ) were compared with age-, type of diabetes-, and sex-matched subjects with diabetes but without an ulcer (n = 36, controls). Total PC was assessed using a routine PC colorimetric assay. There was a significantly (P < 0.001 ) lower level of plasma PC in patients with ulcers (103.3 ± 22.7, mean ± SD) compared with control (127.1 ± 34.0 ) subjects, when corrected for age and matched for gender and type of diabetes. Ulcer type (neuropathic, ischaemic, or mixed) was not a significant covariate for plasma PC levels (P = 0.35 ). There was no correlation between PC levels and gender, type of diabetes, HbA 1 c, or C-reactive protein in either group. In summary, decreased circulating PC levels are associated with, and may predispose to, lower leg ulceration in patients with diabetes.